2013
DOI: 10.1590/s0102-05362013000200006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of five Alocasia species

Abstract: The influence of cytokinin, N6-benzyladenine, on shoot proliferation of five Alocasia species (A. amazonica, A. cuprea, A. robusta, A. longiloba and A. chaii) was investigated. In vitro propagation of these species was established using shoot tip explants. Murashige & Skoog (MS) medium supplemented with different concentrations of BA (N6-benzyladenine) ranging from 0, 2, 5, 10 mg/L was then used to establish the optimum medium for shoot proliferation for all the species. MS medium supplemented with 2.0 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Alocasia longiloba is belongs to Araceae family, which is the most morphologically diverse genera in this family [ 21 , 22 ]. The plant is small to usually robust, evergreen to sometimes seasonally dormant, terrestrial herbs up to 150 cm tall and rhizomatous plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alocasia longiloba is belongs to Araceae family, which is the most morphologically diverse genera in this family [ 21 , 22 ]. The plant is small to usually robust, evergreen to sometimes seasonally dormant, terrestrial herbs up to 150 cm tall and rhizomatous plant.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, micropropagation of A. longiloba was attempted by Bhatt et al [ 22 ] using rhizomes as starting material, however, to the best our knowledge no research study has been conducted using seed as an explant. Here, we aimed to develop an efficient micropropagation protocol for A. longiloba from seed and to compare the antioxidant activity between field-grown plant parts, in vitro-derived greenhouse-grown plant and in vitro derived callus.…”
Section: Introductionmentioning
confidence: 99%
“…But, Thao et al (2003) and Jo et al (2008) observed 100% survival rate in the same soil mixture in case of A. micholitziana and A. amazonica, respectively. Bhatt et al (2013) showed a survival rate of more than 90% in five different species of Alocasia in a mixture containing organic soil and sand in a ratio 1:1. The acclimatized plants were transferred to the larger pots containing garden soil and compost with 1:1 ratio for sufficient growth and finally transplanted to the field.…”
Section: Resultsmentioning
confidence: 99%
“…For this, it is necessary to develop an efficient and economically viable in vitro propagation method to meet the commercial demand for Alocasia species as well as to produce disease-free plants throughout the year (Sanatombi and Sharma 2008). Although the commercial demand for Alocasia species is high, few reports exist on their in vitro propagation (Bhatt et al 2013, Thao et al 2003 and associated protocols (Abdel-Baset et al 2020;Jo et al 2008, Adelberg and Toler 2004. Therefore, in the present research work an attempt was been made for establishing an efficient protocol for the rapid propagation of A. amazonica through indirect shoot organogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Esses resultados são semelhantes aos obtidos por Sreekumar et al (2001), que mostrou a eficiência da aclimatização com seis variedades diferentes de Philodendron as quais obtiveram em média uma taxa de 90% de sobrevivência. Bhatt et al (2013) também mostraram uma taxa de sobrevivência de mais de 90% em cinco espécies diferentes de Alocasia. Para Philodendron bipinnatifidum (Thaumatophyllum bipinnatifidum), as plântulas foram aclimatizadas em mistura de turfa e perlita e obtiveram 100% de sucesso no final da aclimatação (ALAWAADH, 2020), sendo uma espécie de fácil aclimatação, não necessita passar por adaptação antes de ser alocada em casa de vegetação, desempenho semelhante foi observado para a aclimatização de Thaumatophyllum tweedieanum.…”
Section: Aclimatização Das Mudas De Thaumatophyllum Tweedieanumunclassified